Rethinking service recovery: a customer empowerment (CE) perspective - Pranic, Ljudevit; S. Roehl, Wesley (Journal of Business Economics and Management, 2012)
Generally, complainants have been given little power to effect how their service recovery encounter unfolds. Meanwhile, the satisfactory resolution of customer complaints has been a challenging task for many service organizations. Empowering customers in service recovery provides a solution for this challenge. However, the studies on customer empowerment (CE) have taken very narrow perspectives of CE and therefore, none of them individually can explain the nature of CE in service recovery situations among various services that represent the services industry. Based upon the review of the previous research, this article proposes a more integrative theoretical framework in an attempt to better describe and explain the customers’ view of CE in the management of service recovery encounters. According to the proposed model, the degree of complainant-perceived empowerment during service recovery determines both the level of complainant's affective/cognitive responses and the level of subsequent complaint satisfaction. Implications are provided and discussed from both practical and theoretical perspectives.